(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study deals with an analysis of second semester students ability in comprehending reading text. The objective of the study is to investigate the influences of students ability in comprehending text. It used qualitative research. The population of this research is the 2021/2022 second semester students of Indonesia Prima University, Medan. The sample is 32 students. The data of this study are collected by using a test. The test is consisted of 30 questions. The type of the test is an objective test. After collecting the data, then the writer analyzed students’ score. It is found that most of the students unable to comprehend reading text. There are 19 students (59.3%) get score under 65. It makes they really need more attention from the teacher to help them increasing their ability in comprehending the text.